2003
DOI: 10.1590/s0102-86502003000200004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of external gamma radiation on femoral artery reimplantation in rats: morphometrical analyzes

Abstract: Costa RFB, Fagundes DJ, Juliano Y, Novo NF, Vieira WTT. Effects of external gamma radiation on femoral artery reimplantation in rats: morphometrical analyzes. Acta Cir Bras [serial online] 2003 Mar-Apr;18(2). Available from URL: http://www.scielo.br/acb. ABSTRACT -Purpose: To investigate the effects of external gamma radiation on rat femoral artery reimplant. Methods: Sixty-two male Wistar rats were distributed in two groups I (Control) and II (Irradiated), both formed by three observation subgroups: 2 (10 ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…23,[42][43][44] Smaller trials with edifoligide (E2F) decoy oligodeoxynucleotide had shown favourable results in reducing the incidence of NIH. [45][46][47] However, when studied in large, multicenter, randomized trials it has failed to show reduction in the incidence of vein graft failure in patients undergoing CABG as well as lower extremity vein bypass. 48,49 These latter studies on E2F may support the role of remodelling as opposed to pure neointimal growth as the cause of vein graft failure.…”
Section: Inhibition Of Intimal Hyperplasiamentioning
confidence: 99%
“…23,[42][43][44] Smaller trials with edifoligide (E2F) decoy oligodeoxynucleotide had shown favourable results in reducing the incidence of NIH. [45][46][47] However, when studied in large, multicenter, randomized trials it has failed to show reduction in the incidence of vein graft failure in patients undergoing CABG as well as lower extremity vein bypass. 48,49 These latter studies on E2F may support the role of remodelling as opposed to pure neointimal growth as the cause of vein graft failure.…”
Section: Inhibition Of Intimal Hyperplasiamentioning
confidence: 99%